2018
DOI: 10.3126/pravaha.v24i1.20237
|View full text |Cite
|
Sign up to set email alerts
|

Students’ Perception towards Master of Business Studies (MBS) Semester System: A Case Study of Nepal Commerce Campus

Abstract: The study sought to understand and analyze students’ perception towards MBS semester system taking a case of Nepal Commerce Campus with regard to (a) academic resources, (b) course organization and planning, (c) physical resources, (d) governance and image, and (e) overall perception of students. It followed descriptive research design with using questionnaire survey instrument. The population of this study comprised all 668 MBS semester students and the sample consisted 246 students selected through random sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 0 publications
0
12
0
Order By: Relevance
“…These finding are consistent with the work of Perveen and Saeed (2014), Munshi, Javed et al (2012), Ayubbuzder and Ali (2013) who concluded that the informants of their studies also showed discontent with working of the semester examination system. On the contrary, the semester examination system has been found a valid and reliable system in other countries (Dahal 2018). It follows that the problem does not exist with the semester examination system itself rather the improper implementation may be the root cause of the existing problems.…”
Section: Discussionmentioning
confidence: 99%
“…These finding are consistent with the work of Perveen and Saeed (2014), Munshi, Javed et al (2012), Ayubbuzder and Ali (2013) who concluded that the informants of their studies also showed discontent with working of the semester examination system. On the contrary, the semester examination system has been found a valid and reliable system in other countries (Dahal 2018). It follows that the problem does not exist with the semester examination system itself rather the improper implementation may be the root cause of the existing problems.…”
Section: Discussionmentioning
confidence: 99%
“…Zhang and Ahn (2023) study on predicting at-risk students at the Open University in the UK found improved prediction accuracy using identical semester code course data. Dahal (2018) reported student satisfaction with the semester system overall but highlighted issues with facilities like toilets and canteens. Das (2019) demonstrated the effectiveness of the 􀅫lipped classroom method in enhancing learning processes and student satisfaction.…”
Section: Literature Reviewmentioning
confidence: 99%
“…For the last nine years, TU has been implementing a semester system for master's degrees in each faculty from the Central Department of Education, with an expectation to replace the old annual education system through competent performance (Dahal, 2018) among students. However, it has not been found as it was expected.…”
Section: Context Of the Studymentioning
confidence: 99%